The effect of prior cancer on non‐small cell lung cancer trial eligibility. (18th June 2021) - Herman, Michael; Liu, Zhihui; Shepherd, Frances A.; Leighl, Natasha; Liu, Geoffrey; Bradbury, Penelope A.
Abstract: Objectives: Approximately 20% of patients diagnosed with non‐small cell lung cancer (NSCLC) have a history of prior (non‐lung) cancer. Patients with prior cancer are frequently excluded from clinical trials. We aimed to assess the potential impact of prior cancer on commonly used clinical trial endpoints. Materials and Methods: Clinical trials of systemic therapy for incurable NSCLC from clinicaltrials.gov were reviewed to determine the frequency of exclusion on the basis of prior cancer. A cohort of patients with incurable NSCLC and prior cancer, treated with first‐line systemic treatment at our institution were reviewed as a surrogate clinical trial population. A list of priori events was developed to capture the potential for prior cancer to negatively affect clinical trial conduct or endpoints. The proportions of patients that developed an outcome were assessed. Results: Among trials registered on clinicaltrials.gov, 66% listed prior cancer in the eligibility criteria, and of these 35% excluded patients with prior cancer in the last 5 years. Of NSCLC patients treated with systemic therapy at Princess Margaret Cancer Center, 20% had prior cancer, of these, breast (20%) and prostate (19%) were the most common malignancies. Median time between prior cancer and NSCLC was 82 months. Median survival was 20 months. For patients without evidence of active prior cancer at baseline, and not on active therapy for prior cancer, no patients had evidence of a recurrence of prior cancer during the treatment and follow‐up for the NSCLC, nor died from prior cancer. However, two patients developed new primaries. Conclusions: A history of prior cancer has a low likelihood of impacting clinical trial endpoints in patients with incurable NSCLC, if not active or requiring treatment. These findings should be validated in larger data sets. Abstract : Clinical trials frequently exclude patients with prior malignancy from participation. ASCO guidelines recommend increased inclusion of patients with prior malignancies in trials. We have evaluated the frequency that patients with prior malignancies are excluded from clinical trials and evaluated the potential impact of prior malignancy in a cohort of patients with advanced non‐small‐cell lung cancer treated with systemic therapy